Julia Annas. Intelligent Virtue, Oxford, Oxford University Press, 2011, VII + 189 pp. - Crespo, Ricardo (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2012)

(untitled)
Fil: Crespo, Ricardo. Universidad Nacional de Cuyo